MIKROENKAPSULASI PROBIOTIK LACTOBACILLUS RHAMNOSUS FBB81 DAN VIABILITASNYA SELAMA PENYIMPANAN - Komang Ayu Nocianitri; I Nengah Sujaya; Yan Ramona (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2019)
Lactobacillus rhamnosus FBB81 is a probiotic candidate isolated from healthy infant feces that hasfunctional properties as an antioxidant. Probiotics are made in the form of a dry cell bymicroencapsulation technique to facilitate the application of probiotics in the development of functionalfood products. The purpose of this study was to determine the viability of Lb. rhamnosus FBB81encapsulated with maltodextrin and skim milk during storage. The microencapsulated product wasstored at two storage temperatures namely room temperature and cold temperature. The viability of Lb.rhamnosus FBB81 on the microencapsulated product was observed every 1 week for 8 weeks of storage.The results showed that the types of encapsulan and storage temperature affected the viability of Lb.rhamnosus FBB81 during storage. Skim milk and cold temperatures have a better ability than themaltodextrin and room temperature in maintaining the viability of probiotic Lb. rhamnosus FBB81during storage.